1935
DOI: 10.1085/jgp.18.6.905
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin a in Eye Tissues

Abstract: 1. Vitamin A has been found in the retinas and the combined pigment epithelia and choroid layers of frogs, pigs, sheep, and cattle. The vitamin was identified by (a) its specific absorption at 328 mµ; (b) the blue color yielded with antimony trichloride, associated with an absorption band at about 620 mµ; (c) anti-xerophthalmic and growth-promoting activity; and (d) quantitative relationships among the results of these three types of observation. 2. The mammalian retinas contain about 22γ, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1935
1935
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Its mechanism of action was elucidated by the work of many researchers over a period of more than a century (2)(3)(4). In fact, the last landmark discovery in visual photoreception was the cloning of human genes encoding the blue, green, and red opsins in 1986 (5).…”
Section: Historical Perspectivementioning
confidence: 99%
“…Its mechanism of action was elucidated by the work of many researchers over a period of more than a century (2)(3)(4). In fact, the last landmark discovery in visual photoreception was the cloning of human genes encoding the blue, green, and red opsins in 1986 (5).…”
Section: Historical Perspectivementioning
confidence: 99%
“…The all-trans-retinal dissociates from opsin in a series of steps called photo-bleaching. The final stage is conversion of 11-cis-retinal rebind to opsin to reform rhodopsin in the retina [15][16][17] . Kuhne showed that rhodopsin in the retina is only regenerated when the retina is attached to retinal pigmented epithelium (RPE) 17 .…”
Section: Vision Cyclementioning
confidence: 99%
“…Another shared feature among the animal kingdom is the ability for all visual pigments to signal multiple light events. This continued transduction depends on the regeneration of the visual chromophore 1‐4 . In the vertebrate retina, the re‐isomerization of at‐RAL to 11c‐RAL occurs in the retinal pigment epithelium (RPE), a monolayer of cells directly adjacent to the photoreceptors, in a process known as the visual (retinoid) cycle 5,6 .…”
Section: Introductionmentioning
confidence: 99%